Dynamic Characteristics of a Rotating Blade with a Dovetail Fixture - Xiaoyu Fan; Wenchao Liang; Jin Zeng; Yang Yang; Hui Ma; Chenguang Fan; Shunguo Fu (Machines, 2023)
Considering rotation-induced centrifugal stiffening, spin softening, and Coriolis effects, the reduced dynamic model of a rotating blade with a dovetail fixture is established in the ANSYS environment via the fixed-interface method for higher computational efficiency and lower memory consumption. Then some parameters such as rotating speed, friction factor, and stator blade number affecting the nonlinear vibration responses of the system under the combined actions of aerodynamic force, centrifugal force, and gravity are elaborately discussed. The results show that: (1) the contact-induced nonlinearity between the tenon and the mortise mainly results in the frequency multiplications of the aerodynamic excitation frequency; (2) a larger friction factor results in a lower magnitude of contact pressure and a higher resonance frequency, while a larger stator blade number results in a lower magnitude of the uniform and continuous contact pressure distribution; (3) the excitation of the resonant mode caused by the aerodynamic force is primarily characterized by the first-order bending mode of the system.